Markers of infection, breast-feeding and childhood acute lymphoblastic leukaemia - Infante-Rivard, C (Nature Publishing Group, 2000)
Infections are suspected to play a role in the aetiology of childhood leukaemia. In 1989–95, we evaluated the relation between childhood acute lymphoblastic leukaemia and pre- and postnatal markers of exposure to infection, as well as breast-feeding. A population-based case-control study was carried out in certain regions of Québec, Canada, in 1989–95 including 491 incident cases diagnosed between 1980 and 1993 and aged between 0 and 9 years. An identical number of healthy controls matched for age, sex and region of residence at the date of diagnosis was included. Having older siblings, mother's use of antibiotics during pregnancy, and being born second or later were all associated with increased risk of leukaemia while early day-care attendance (odds ratio (OR) = 0.49; 95% CI 0.31–0.77), and breast-feeding (OR = 0.68; 95% CI 0.49–0.95) were significantly protective. A marker of population mixing was not a risk factor. When including all variables defining family structure in a model, having older siblings at time of diagnosis was a risk factor among children diagnosed before 4 years of age (OR = 4.54; 95% CI 2.27–9.07) whereas having older siblings in the first year of life was protective among children diagnosed at 4 years of age or later (OR = 0.46; 95% CI 0.22–0.97). © 2000 Cancer Research Campaign http://www.bjcancer.com